PERBANDINGAN PENGARUH LATIHAN RAPID FIRE DENGAN LATIHAN WALL PASSING CIRCUIT TERHADAP KEMAMPUAN CHEST PASS DALAM PERMAINAN BOLABASKET TIM PUTRI SMAN 6 PEKANBARU - Maiwahyudi '; Ramadi '; Ardiah Juita Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract The results indicate that there are problem identification exercises that can have a significant influence on the ability of a chest pass in basketball games. Issues raised in this study is the effect of exercise Is there a difference in rapid fire wall passing drills sircuit premises of the ability of a chest pass in basketball games girls team SMAN 6 Pekanbaru? The research hypothesis proposed in this study is that there is a difference the effects of exercise training premises rapid fire wall sircuit passing on the ability of a chest pass in basketball games girls team SMAN 6 Pekanbaru. This study aimed to compare the effects of exercise training premises rapid fire wall sircuit passing on the ability chest pass in basketball games girls team SMAN 6 Pekanbaru. This study is experimental. The study was conducted on women's basketball team from SMAN 6 Pekanbaru. Data were obtained and collected through the initial test (pretest) before being given treatment and final test (posttest) after being given the treatment as much as 16 times with a frequency of 3 times in one week. Data were analyzed by using a comparative analysis of statistical data.The results of the analysis showed that there was no difference in the effects of exercise training premises rapid fire wall sircuit passing on the ability of a chest pass in basketball games girls team SMAN 6 Pekanbaru. Based on the statistical data analysis of comparative yield of 0.40 t count and ttable of 1,812. Means thitung smaller than ttable so it can be concluded that there are no differences in the effect of the exercise of the ability of a chest pass in basketball game, in other words both are equally effective exercise influence on the ability of a chest pass in basketball game. Keywords: Rapid Fire Training, Wall Passing Circuit Training, Chest Pass.